Synthesis and characterization of transition metal ion doping on the photocatalytic activity of TiO2 nanoparticles - N. Wetchakun (2018)
Transition metal ion (V, Fe, or Cu) doped TiO2 nanoparticles were synthesized from titanium tetraisopropoxide (TTIP) in absolute ethanol by the modified sol-gel method. The precursor of the transition metal to be doped was added to an alcoholic solution containing TTIP. This solution was loaded into a pouch type cellophane membrane and placed in a clear solution containing 1:1 (v/v) ratio of absolute ethanol and distilled water with 0.5-1.0% concentrated ammonia solution for 1h. After the completion of the dialysis process (1h), the suspension was centrifuged (7500 rpm, 10 min), washed with milli-Q water and then dried in an oven at 60°C for 24h. The powder was finally calcined in a furnace at a temperature of 400°C for 3h. The use of cellophane membrane offered the advantage of a well-controlled diffusion rate. UV-Vis absorption studies confirmed that the spectral responses of metal ion doped TiO2 were shifted to the visible light region. Phase composition, crystallinity, crystal size and morphology of V, Fe, and Cu doped TiO2 nanopaticles were examined by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The crystalline size of V, Fe, Cu doped TiO2 nanopaticles was found to be in the range of 10-20 nm. The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on V-, Fe-, and Cu-doped TiO2 nanoparticles. The photocatalytic activities of the various doped samples were evaluated by studying the mineralization of sucrose, phenol, oxalic acid, formic acid, methanol, and malonic acid under UVA, solar spectrum, and visible light irradiation. Under UVA and solar spectrum illumination, bare TiO2 outperformed all doped TiO2 photocatalysts in mineralizing the various organic compounds. Under visible light illumination, it was found that Fe-doped TiO2 nanoparticles could significantly mineralize only oxalic acid. This indicates that the enhanced performance of the Fe-doped TiO2 nanoparticles might not be due to the red shift of the semiconductor. It is likely due to the formation of the easily photolyzed ferrioxalate complex. Various factors such as particle size, crystallinity, and amount of transition metal ion dopant in TiO2 were evaluated for the enhancement of the photocatalytic activity. © 2008 IEEE.